Vitamin D supplementation alleviates diabetic complications by increasing the amount of irisin in testicular tissues and blood of rats with experimental diabetes - Yalcin, M. H.; Girgin, A.; Ugur, K.; Karagoz, Z. K.; Aydin, S.; Karabulut, B.; Aydin, S. (Verduci Publisher, 2023)
OBJECTIVE: Diabetes is an im-portant endocrinological disease that has an in-creasing incidence in the world and affects all biological tissues including testicles. Therefore, this study aimed to reveal the histological and biochemical effects of vitamin D on irisin, apop-tosis, total antioxidant status (TAS), and total ox-idant status (TOS) in testicular tissues of rats with experimental diabetes.MATERIALS AND METHODS: 41 male Wis-tar rats, 8-10 weeks old, weighing between 200-220 g, were included in the study as the follow-ing groups: control group (n=7; no treatment), sham group [only sodium citrate buffer (SCB)] [n=7; single dose 0.1 Molar (M) SCB given intra-peritoneally (i.p)], vitamin D group (n=7; 50 IU/ day given orally), diabetes group [n=10; single dose 50 mg/kg Streptozotocin (STZ) dissolved in 0.1 M SCB and given i.p (tail vein blood glucose level above 250 mg/dl after 72 hours)] and diabe-tes+vitamin D group [n=10, single dose 50 mg/ kg STZ, dissolved in 0.1 M SCB and given i.p (tail vein blood glucose level above 250 mg/dl after 72 hours) and when diabetes occurs, oral vita-min D administration of 50 IU/day)]. At the end of the 8 weeks experiment, blood was drawn from the tail vein of all rats, they were sacrificed and testicular tissues were taken. While the amount of irisin in the blood and testicular tissue supernatants was analyzed with the Enzyme-Linked Immunosorbent Assay (ELISA) method, TAS and TOS measurements were analyzed with the REL method, testicular tissues were analyzed his-topathologically, immunohistochemically, and with the TUNEL method.RESULTS: When the diabetes group was com-pared with the control and sham groups, it was reported that the amounts of blood and tissue su-pernatant irisin and TAS significantly decreased and the TOS was significantly increased; a sta-tistically significant increase in irisin and TAS of blood and tissue supernatants and a signifi-cant decrease in TOS were detected when dia-betes+vitamin D and diabetes groups were com-pared among themselves. Similar results were obtained in the immunohistochemical studies. Tissue expressions of irisin decreased in the di-abetes group compared to the control and sh-am groups, while the application of vitamin D increased the tissue expressions of irisin. Ad-ditionally, when the numbers of apoptotic cells were compared, it was reported that apoptotic cells in the diabetes group increased significant-ly compared to the control and sham groups, and vitamin D administration significantly de-creased the number of apoptotic cells.CONCLUSIONS: Taken together, vitamin D ad-ministration to diabetic rats decreased the number of apoptotic cells and increased the amount of irisin. Vitamin D had an effective role in main-taining the physiological integrity of rat testicu-lar tissues, so vitamin D may be a potent agent to be used in the treatment of diabetes in the future.
Keywords: Experimental diabetes; Testis; Irisin; Vitamin D; Apop-tosis